Pembaruan pemikiran hukum keluargaIslam di Indonesia - Ismail Ismail (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2011)
Islamic family law or ahwal al-shakhsiyyah has prevailed in Indonesia since the inception of the law no. 1year 1974 concerning with marriage and the compilation of Islamic law in Indonesia (KHI) in 1991.Islamic family law run in Indonesia is not exactly the same as those contained in the books of classicaljurisprudence (fiqh). From its materials has been found in the legislation, there are a number of newprovisions that was different from those classical Islamic jurisprudence such as in marriage record, agerestrictions of marriage, polygamy, inheritance and wasiah wajibah etc.  These new provisions were issuedby scholars and contemporary Islamic jurists in the context of law reform.